Android-Based Network Services Application Learning Media for Vocational High Schools - Dony Novaliendry (International Association of Online Engineering (IAOE), 2021)
Digital and communication technology has developed in combination with globalization to ensure quick connectivity and distribution of information. In particular, the quality of education is one of the education challenges that have become a target for urgent solutions.  From the various conditions and potentials that exist, efforts that can be made concerning quality improvement in schools are to develop a student-oriented learning system (children center) and facilitate student’s needs for learning needs that are challenging, active, creative, innovative, practical, and fun by developing and apply learning based on Information and Communication Technology. This research was generated using the media development method, which refers to Four-D development, which consists of four stages: Define, Design, Develop, and Disseminate, carried out in high school. Vocational class XI Computer and Network Engineering. In this study, the test subjects were students of class XI Computer and Network Engineering at SMK Negeri 8 Padang. The three validator’s assessment as a whole, the validator test assessment of Android-Based Learning Media is 94.28%. The validity level can be interpreted as being Very Valid to use. Overall, the practicality assessment of Android-Based Learning Media as a learning resource is 88.46%, so that the level of practicality can be interpreted as Very Practical to use. The evaluation of Android-Based Learning Media's effectiveness of 90.86%, so that the level of significance can be interpreted as Very Good for use.